The Effect of Expressive Writing Programs on Post-Traumatic Stress Disorders Symptoms in Female Victims of Domestic Violence - Ayu Dyah Hapsari; Sofia Retnowati (Universitas Negeri Malang, 2020)
The purpose of this study was to determine the effect of expressive writing on the symptoms of posttraumatic stress disorder in female victims of domestic violence. This research uses quasi-experimental methods (using the untreated control group design). Participants in this study were 10 women who are victims of domestic violence. Participants were assigned into two groups, experimental and control groups. The results showed that there was a significant effect between experimental group posttest scores with the control group (p=0,043), which means that the research hypothesis was accepted. From the results of this study also found that there is a decrease in scores of symptoms of posttraumatic stress disorder which measured using the Impact of Events Scale-Revised (IES-R) in participants in the experimental group.Keywords: expressive writing; symptoms of posttraumatic stress disorder; domestic violence.